Effect of Aerobic and Anaerobic Exercise on the Complement System of Proteins in Healthy Young Males - Kostrzewa-Nowak, Dorota (J Clin Med, 2020)
This study was aimed at examining the impact of common types of physical efforts used to determine the aerobic and anaerobic performance of the participants on the complement system in their peripheral blood. Fifty-one physically active young males aged 16 years old (range 15–21 years) were divided into two age groups (younger, 15–17 years old and older, 18–21 years old) and performed two types of intensive efforts: aerobic (endurance; 20-m shuttle run test; Beep) and anaerobic (speed; repeated speed ability test; RSA). Venous blood samples were collected before and after each exercise (5 and 60 min) to profile the complement system components, namely the levels of C2, C3, C3a, iC3b, and C4. The endurance effort caused a decrease in the post-test C3 (p < 0.001 for both age groups) and increase in post-test C3a (p < 0.001 and p < 0.01 for the younger and older group, respectively), recovery iC3b (p < 0.001 and p < 0.05 for younger and older group, respectively), recovery C2 (p < 0.01 for both age groups), and post-test C4 (p < 0.05 and p < 0.01 for the younger and older group, respectively) levels, while the speed effort caused a decrease only in the post-test C2 (p < 0.05 for younger participants) and post-test C4 levels (p < 0.001 and p < 0.01 for the younger and older group, respectively) and an increase in the recovery C3a level (p < 0.05). Our study provides evidence that different types of physical effort promote different immune responses in physically active young men. Aerobic exercise induced the activation of an alternative pathway of the complement system, whilst the anaerobic effort had little influence. A better understanding of the post-exercise immune response provides a framework to prescribe physical activity to achieve different health outcomes.